Dzieje Katedry Ekonomii Politycznej na Wydziale Prawa Uniwersytetu Wrocławskiego w latach 1945–1956 - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The Department of Political Economy at the Faculty of Law, University of Wrocław, went through an extremely important and turbulent period in 1945–1956. It was a time of building the Department and of its scholarly development. The main role in the Department was played by Professor Wincenty Styś, almost from the very beginning persecuted by the communist authorities. A characteristic feature of the Department were frequent changes of auxiliary academic staff. In addition to lectures on political economy and economic history, the academics working at the Department also lectured on ideological subjects Marxism, both at the Faculty of Law and other faculties at the University of Wrocław. That is why the Department was more politicised and the authorities interfered in its work more often than in the case of other departments. Most staff, in addition to working at the Department, were also employed at the School of Business and then School of Economics in Wrocław.
Keywords: ekonomia polityczna; Katedra Ekonomii Politycznej; przedmioty ideologiczno-polityczne; Uniwersytet Wrocławski; Styś, Wincenty (1903-1960); Wydział Prawa